ANALISIS PENYEBAB INTERNAL KEBANGKRUTAN PT SRI REJEKI ISMAN TBK: STUDI KASUS PAILIT DAN IMPLIKASINYA TERHADAP INDUSTRI TEKSTIL DI INDONESIA - Fansiska, Claudya (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
Bankruptcy occurs when a company is unable to fulfill its financial obligations promptly. This study aims to analyze the impact of PT Sri Rejeki Isman Tbk (Sritex) bankruptcy on the Indonesian textile industry, identify the internal factors that contributed to this situation, and explore the legal processes the company underwent. Utilizing a normative legal research method with a regulatory approach, the findings reveal that Sritex's bankruptcy has had significant repercussions for the national textile sector, including the loss of thousands of jobs, disruptions in the supply chain, and a decline in international competitiveness. Primary internal factors leading to the bankruptcy include ineffective debt management and inadequate crisis management. The legal proceedings involved filing a bankruptcy petition and asset management by a curator. This study provides valuable insights into the broader effects of substantial corporate bankruptcies on economic strategies and underscores the urgent need for enhanced financial and risk management practices.